2003
DOI: 10.1521/scpq.18.2.122.21854
|View full text |Cite
|
Sign up to set email alerts
|

Hope theory, measurements, and applications to school psychology.

Abstract: The tenets of a cognitive, motivational model called hope theory (Snyder et al., 1991) are reviewed, along with the two accompanying instruments for measuring hope in children and adolescents. More than a decade of research on hope theory as it relates to students, teachers, and schools is summarized. Likewise, the applications of hope theory for school psychologists are reviewed.School psychologists contribute greatly in helping students, teachers, and schools in general to become more hopeful. As such, we se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
180
3
16

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(207 citation statements)
references
References 54 publications
8
180
3
16
Order By: Relevance
“…Bunlar; açık amaçların ve işlevsel yolların belirlenmesi ve önleyici amaçları gerçekleştirmeye yönelik güdülenmedir. Umutlu düşünce sadece ruh sağlığı alanında değil, ayrıca eğitim alanında da önemli bir yere sahiptir (Snyder vd., 1991;Snyder, Lopez, Shorey, Rand ve Feldman, 2003). Snyder ve diğerleri (2002) umut kuramının eğitim alanında güdüleyici bir model olarak kullanılmasının öneminin altını çizmişlerdir.…”
Section: Introductionunclassified
“…Bunlar; açık amaçların ve işlevsel yolların belirlenmesi ve önleyici amaçları gerçekleştirmeye yönelik güdülenmedir. Umutlu düşünce sadece ruh sağlığı alanında değil, ayrıca eğitim alanında da önemli bir yere sahiptir (Snyder vd., 1991;Snyder, Lopez, Shorey, Rand ve Feldman, 2003). Snyder ve diğerleri (2002) umut kuramının eğitim alanında güdüleyici bir model olarak kullanılmasının öneminin altını çizmişlerdir.…”
Section: Introductionunclassified
“…In other words, hope comprises "willpower" and "waypower" thinking of how individual determinates his/her goals by former and being able to create alternative pathways and contingency plans to achieve a goal with barriers by latter. Similar to self-efficacy and optimism, hope has become an essential coping strategy in academic context (Onwuegbuzie & Snyder, 2000 ;Snyder, Lopez, Shorey, Rand, & Feldman, 2003) as researchers have investigated its importance for research and practice that students with high level of hope were found to correlate positively with academic achievement (McDermott & Snyder, 2000).…”
Section: Hopementioning
confidence: 99%
“…A review of hope (e.g., Snyder, 1994Snyder, , 2000Snyder et al, 1997;Snyder, Sympson, Ybasco, Borders, & Babyak, 1996) and response expectancy (e.g., Kirsch, 1999) assessment literatures revealed at least two main limitations.…”
Section: Introductionmentioning
confidence: 99%